The Impact of Applying Governance Mechanisms on Corporate Social Responsibility Disclosure in Saudi Banks - Alsayegh, Maha Faisal; Aljuaid, Nawal Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aims to examine the impact of applying governance mechanisms on corporate social responsibility disclosure (hereafter CSRD) in Saudi banks. Governance mechanisms exemplified in board size, board Independence, audit committee size, and audit committee meeting frequency were examined. To achieve the aim of this study, a descriptive analytical approach has been employed in which the researchers have analyzed the annual reports of the banks under investigation for the period 2018-2021. Also, an index consisted of 26 items of corporate social responsibility were built to measure CSRD in the examined banks. In addition, a multiple linear regression was used to test the study performed hypothesis. Results showed that there was a statistically significant impact of board size, and audit committee size on CSRD in Saudi banks. It showed also that there was no statistically significant impact of board independence and audit committee meeting frequency on CSRD in Saudi banks. In addition, results showed that there was a positive correlation between board size, audit committee size, and CSRD. Results also showed a positive correlation between board Independence and CSRD but it was non-significant. The study recommended that regulators should establish and develop an index for the disclosure of corporate social responsibility to guide companies and researchers who are interested in CSRD studies. It is suggested for future research to study the effect of different governance mechanisms than the one used in this study on CSRD and to focus on the type and quality of disclosure.